II. Mr. Lerner's Supplementary Limits for Price Index Numbers - Joseph, M. F. W. (Review of Economic Studies, 1936)
Journal Article Further Notes on Index Numbers: II. Mr. Lerner's Supplementary Limits for Price Index Numbers Get access M. F. W. Joseph M. F. W. Joseph Geneva Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 155–157, https://doi.org/10.2307/2967511 Published: 01 February 1936